2014
DOI: 10.1007/s00059-014-4175-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of visceral adiposity index for type 2 diabetes mellitus

Abstract: VAI could independently predict DM in the Chinese study population, although the predictive power was not higher than that of simple anthropometric measures (BMI and WC). Our study does not support the clinical application of VAI; however, more studies based on different ethnic groups still need to be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 22 publications
8
30
3
1
Order By: Relevance
“…Our results differed from those of a previous cohort study in China [17] , which reported that compared to other indices for body fatness measurements, VAI was a better and convenience surrogate marker for visceral adipose measurement and could be used in identifying the risk of diabetes in largescale epidemiologic studies. However, our results were consistent with the 7-year follow-up data in Iranian [54] and 15-year prospective cohort study in China [18] , which indicated that although VAI could independently predict future diabetes, its discriminatory power was not better than simple anthropometric measures such as BMI, WC and WHtR [33] . However, it should be pointed out that the sample size in the 15-year prospective cohort study among Chinese population was relatively small, it only compared the VAI with BMI and WC (not include WHR and WHtR), and the relationship between VAI and diabetes risk was not examined in different genders [18] .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our results differed from those of a previous cohort study in China [17] , which reported that compared to other indices for body fatness measurements, VAI was a better and convenience surrogate marker for visceral adipose measurement and could be used in identifying the risk of diabetes in largescale epidemiologic studies. However, our results were consistent with the 7-year follow-up data in Iranian [54] and 15-year prospective cohort study in China [18] , which indicated that although VAI could independently predict future diabetes, its discriminatory power was not better than simple anthropometric measures such as BMI, WC and WHtR [33] . However, it should be pointed out that the sample size in the 15-year prospective cohort study among Chinese population was relatively small, it only compared the VAI with BMI and WC (not include WHR and WHtR), and the relationship between VAI and diabetes risk was not examined in different genders [18] .…”
Section: Discussionsupporting
confidence: 81%
“…However, our results were consistent with the 7-year follow-up data in Iranian [54] and 15-year prospective cohort study in China [18] , which indicated that although VAI could independently predict future diabetes, its discriminatory power was not better than simple anthropometric measures such as BMI, WC and WHtR [33] . However, it should be pointed out that the sample size in the 15-year prospective cohort study among Chinese population was relatively small, it only compared the VAI with BMI and WC (not include WHR and WHtR), and the relationship between VAI and diabetes risk was not examined in different genders [18] . Thus, our study revealed that although the prediction ability of diabetes risk for VAI was unlikely to be higher than other fatness indices, VAI could be a simple measure of visceral obesity for predicting the risk of diabetes among Chinese adults, especially among women.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…VAI is a marker of visceral adipose dysfunction and is strongly associated with cardiovascular events and type 2 diabetes (12,30,31). VAI is significantly correlated with inflammation and insulin resistance in patients with type 2 diabetes and cardiovascular disorders (12,32).…”
Section: Vai and Tg/hdl Ratio In Hypogonadismmentioning
confidence: 99%